Seke phonology: a comparative study of three Seke dialects - Honda, Isao (2024)
The Seke language is a member of the Tamangic group, which also includes Tamang, Gurung, Thakali, Manangba, Nar-Phu, and Chantya1.1 The existence of this language has been reported in many articles, both ethnographical and linguistic? However, there has not been much research on the language itself.3 Despite the fact that Fiirer-Haimendorf (1975) already pointed out that this language is similar to Thakali (see also Gauchan & Vinding 1977:101), it is still often considered to be a dialect of the Tibetan language.